Hypothermia during partial nephrectomy for patients with renal tumors: a randomized controlled trial - Breau, RH; Fergusson, DA; Knoll, G; McAlpine, K; Morash, C; Cnossen, S; Lavallée, LT; Mallick, R; Finelli, A; Jewett, MAS; Leibovich, BC; Cook, JA; et al. (Lippincott, Williams & Wilkins, 2020)
Background: Surgeons induce renal hypothermia during partial nephrectomy to preserve kidney function, without strong evidence of benefit. This trial examined the effectiveness and safety of renal hypothermia during partial nephrectomy.